Turbulence measurement with a propeller flow meter - Bennett, J. P., author; U.S. Geological Survey, publisher (Colorado State University. Libraries, 1968)
There is a pressing need in much of the current Hydraulic Engineering research being conducted today for an easy, reliable, and cheap method for measuring longitudinal turbulent velocity fluctuations in water flows. Hot-film anemometers can be used in clean water flows, however, drift problems, fragileness, and expensiveness sometimes prevent their use in sediment and debris laden streams. The propeller flow meter is a rugged, portable, relatively inexpensive flow measuring device which can be used to measure turbulence in large scale flows. It has two drawbacks when used as a turbulence measuring device, however. These are 1) inertial averaging, and 2) spatial averaging of the turbulent velocity fluctuations. These factors can be corrected for in the power spectral density of a particular turbulent flow phenomenon if the propeller system function and spectral recovery efficiency are known. In this study, a propeller equation of motion is developed which describes the inertial averaging characteristics of propellers. A correlation function is developed which describes the spatial averaging effect on a particular propeller in a particular flow field, if the required statistical properties of the flow field are known. Due to the complexity of the coefficients in the differential equation of motion of a propeller, experimental means were used in determining these coefficients. Similarly, the spatial averaging characteristics had to be determined experimentally for a particular type of turbulent flow, rough boundary open channel flow. The experimentally determined system functions were used to correct field turbulence data for inertial averaging. It appears that propellers of the size used in this study can be used in open channel flows of three feet in depth with very little correction required.
CER68-69-JPB-41.
Open-file report.
September 1968.
Keywords: Turbulence -- Measurement; Propellers